2003
DOI: 10.1007/s00204-002-0435-6
|View full text |Cite
|
Sign up to set email alerts
|

AM404 and VDM 11 non-specifically inhibit C6 glioma cell proliferation at concentrations used to block the cellular accumulation of the endocannabinoid anandamide

Abstract: AM404 [ N-(4-hydroxyphenyl)arachidonylamide] and VDM 11 [(5 Z,8 Z,11 Z,14 Z)- N-(4-hydroxy-2-methylphenyl)-5,8,11,14-eicosatetraenamide] are commonly used to prevent the cellular accumulation of the endocannabinoid anandamide, and thereby to potentiate its actions. However, it has been reported that AM404 can produce an influx of calcium into cells, which might be expected to have deleterious effects on cell proliferation. In the present study, AM404 and VDM 11 were found to reduce C6 glioma cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Various cannabinoids, including cannabidiol, anandamide, and 2-AG, and endocannabinoid transport inhibitors have been shown to induce apoptotic cell death and to inhibit proliferation and migration in numerous murine and human tumor cell lines including glioma (C6, U87, U373, and H4), oligodendroglioma (Gos3), glioblastoma multiforme, astrocytoma (U373-MG, U87MG, and human grade IV astrocytoma), neuroblastoma (N18 TG2 and CHP100), pheochromocytoma (PC12), breast cancer (MCF-7, EFM-19, T47D, TSA-E1, and MDA-MB-231), prostate cancer (LNCaP, DU145, and PC3), colon carcinoma (SW 480), uterine cervix carcinoma (CxCa), thyroid cancer (KiMol), leukemia (CEM, HEL-92, HL60, and Jurkat cell lines), and lymphoid tumors (EL-4 and P815) tumor cells via CB 1 /CB 2 -and VR 1 receptor-dependent or independent (e.g., cyclooxygenase) mechanisms Sá nchez et al, 1998Sá nchez et al, , 2003Jacobsson et al, 2000;Maccarrone et al, 2000b;Sarker et al, 2000;McKallip et al, 2002a,b;Fowler et al, 2003;Jonsson et al, 2003;Mimeault et al, 2003;Bifulco et al, 2004;Contassot et al, 2004a,b;Hinz et al, 2004;Joseph et al, 2004;Kogan et al, 2004;Massi et al, 2004;Nithipatikom et al, 2004;Allister et al, 2005;EllertMiklaszewska et al, 2005;Herrera et al, 2005Herrera et al, , 2006Lombard et al, 2005;Powles et al, 2005;Sarfaraz et al, 2005;Vaccani et al, 2005;Carracedo et al, 2006;430 Grimaldi et al, 2006;Ligresti et al, 2006b). More importantly, systemic or local treatment with cannabinoids inhibited the growth of various types of tumor or tumor cell xenografts in vivo, including lung carcinoma (Munson et al, 1975), glioma Sá nchez et al, 2001a;Massi et al, 2004), thyroid epithelioma …”
Section: F Cancermentioning
confidence: 99%
“…Various cannabinoids, including cannabidiol, anandamide, and 2-AG, and endocannabinoid transport inhibitors have been shown to induce apoptotic cell death and to inhibit proliferation and migration in numerous murine and human tumor cell lines including glioma (C6, U87, U373, and H4), oligodendroglioma (Gos3), glioblastoma multiforme, astrocytoma (U373-MG, U87MG, and human grade IV astrocytoma), neuroblastoma (N18 TG2 and CHP100), pheochromocytoma (PC12), breast cancer (MCF-7, EFM-19, T47D, TSA-E1, and MDA-MB-231), prostate cancer (LNCaP, DU145, and PC3), colon carcinoma (SW 480), uterine cervix carcinoma (CxCa), thyroid cancer (KiMol), leukemia (CEM, HEL-92, HL60, and Jurkat cell lines), and lymphoid tumors (EL-4 and P815) tumor cells via CB 1 /CB 2 -and VR 1 receptor-dependent or independent (e.g., cyclooxygenase) mechanisms Sá nchez et al, 1998Sá nchez et al, , 2003Jacobsson et al, 2000;Maccarrone et al, 2000b;Sarker et al, 2000;McKallip et al, 2002a,b;Fowler et al, 2003;Jonsson et al, 2003;Mimeault et al, 2003;Bifulco et al, 2004;Contassot et al, 2004a,b;Hinz et al, 2004;Joseph et al, 2004;Kogan et al, 2004;Massi et al, 2004;Nithipatikom et al, 2004;Allister et al, 2005;EllertMiklaszewska et al, 2005;Herrera et al, 2005Herrera et al, , 2006Lombard et al, 2005;Powles et al, 2005;Sarfaraz et al, 2005;Vaccani et al, 2005;Carracedo et al, 2006;430 Grimaldi et al, 2006;Ligresti et al, 2006b). More importantly, systemic or local treatment with cannabinoids inhibited the growth of various types of tumor or tumor cell xenografts in vivo, including lung carcinoma (Munson et al, 1975), glioma Sá nchez et al, 2001a;Massi et al, 2004), thyroid epithelioma …”
Section: F Cancermentioning
confidence: 99%
“…Of further interest is the possibility that the endocannabinoid system represents one of the defense mechanisms of the body against cancer proliferation. The treatment of cancer cells with VDM11 and AA-5-HT which inhibit anandamide transport into the cell and anandamide hydrolysis respectively, potentiate anandamide-mediated inhibition of C6 glioma cell proliferation [85]. They are also able to inhibit KiMol tumor growth in-vivo, by enhancing intratumoral endocannabinoids levels [114].…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, they inhibited C6 cell proliferation by a non CB1/CB2/vanilloid mechanism, as their action was prevented neither by cannabinoid nor by vanilloid receptor antagonists. The antioxidant α-tocopherol, which, as mentioned above, prevents death induced by anandamide [35], likewise had no effect [85]. However, in a recent study it was shown that in thyroid epithelioma cells, the CB1 antagonist SR141716A (Fig.…”
Section: Cannabinoid Actions On Glioma Cells That Are Not Through Thementioning
confidence: 95%
“…While the anti-proliferative effect of the eCBs is blocked by cannabinoid receptor antagonists, the antiproliferative effect of synthetic agonists was not [58]. Interestingly, AEA also induces apoptosis in a variety of human glioma cell lines through TRPV1 [58,[60][61][62], and chemical disruption of lipid rafts blocks this effect [63]. Several other cannabinoids have also been shown to induce apoptosis in C6 cells, including the eCB analogue stearoylethanolamide [64,65].…”
mentioning
confidence: 97%